Characterization of interactions of lipoquinone derivatives within model membrane systems - Bublitz, Gaia Rachel, author; Crans, Debbie, advisor; Cohen, Robert, advisor; Santangelo, Thomas, committee member; Roess, Deborah, committee member (Colorado State University. Libraries, 2021)
Menaquinones (MK) are electron carriers composed of a naphthoquinone moiety and an isoprene side chain of variable length and saturation. These molecules are the only quinone derivatives present in the electron transport systems of all Gram-positive bacteria and some Gram-negative anaerobes. Subsequently, MK plays a critical role in respiration for pathogens such as Staphylococcus aureus and Mycobacterium tuberculosis. Although the physiological function and relevance of MK as a redox cofactor have been established, its chemical interactions within the plasma membrane and the effects of these properties on MK-mediated electron transport are still obscure. These unknowns are reflected in existing literature, as MK is commonly depicted in an extended conformation, although in vitro and in vivo studies suggest that biomolecules with alkyl moieties assume folded conformations in native environments (Ko et al., 2011; Trembleau et al., 2003). In this study, we implemented 1D 1H and 2D 1H-1H NMR spectroscopic techniques to characterize the location and 3D conformation of MK-2 within a L-α-phosphatidylcholine liposome model. MK-2, a truncated menaquinone analog, was selected due to its limited rotational variability and previous characterization in a simple monolayer lipid system (Koehn et al., 2018). Our data suggests that MK-2 is largely incorporated into the phospholipid bilayer, with an aqueous subspecies residing at the polar membrane interface in a concentration-dependent manner. 2D NOESY spectroscopic analysis supports the interpretation that both the aqueous form and the membrane-associated form of MK-2 assume a folded conformation. These findings provide a reference for the study of the properties of MK derivatives with longer isoprene chains, which are analogous to functional MK variants in native environments.